2000
DOI: 10.1159/000028402
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacogenetics of the Human Arylamine N-Acetyltransferases

Abstract: This review briefly describes current understanding of one of the earliest discovered pharmacogenetic polymorphisms of drug biotransformation affecting acetylation of certain homo- and heterocyclic aromatic amines and hydrazines. This so-called acetylation polymorphism arises from allelic variation in one of the two known human arylamine N-acetyltransferase genes, namely NAT2, which results in production of NAT2 proteins with variable enzyme activity or stability. The NAT1 gene locus encodes a structurally rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
26
0
1

Year Published

2001
2001
2012
2012

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(27 citation statements)
references
References 42 publications
0
26
0
1
Order By: Relevance
“…119,120 Isoniazid was the first NAT2 substrate for which acetylation polymorphism with its well-known bimodal distribution was described following the observation that peripheral neuropathy, a potential side effect of the drug, is subject to interindividual variation depending on patients' acetylation capacity. 121 Tiittinen et al 122 could demonstrate that the metabolism of isoniazid varies interindividually, with mean apparent elimination half-lives of 80 min for rapid acetylators and 180 min for slow acetylators. Subsequently, these earlier findings were complemented by genotyping studies showing a linear relationship of isoniazid pharmacokinetic parameters to the number of highly active NAT2 genes.…”
Section: Tuberculosis and Isoniazidmentioning
confidence: 99%
“…119,120 Isoniazid was the first NAT2 substrate for which acetylation polymorphism with its well-known bimodal distribution was described following the observation that peripheral neuropathy, a potential side effect of the drug, is subject to interindividual variation depending on patients' acetylation capacity. 121 Tiittinen et al 122 could demonstrate that the metabolism of isoniazid varies interindividually, with mean apparent elimination half-lives of 80 min for rapid acetylators and 180 min for slow acetylators. Subsequently, these earlier findings were complemented by genotyping studies showing a linear relationship of isoniazid pharmacokinetic parameters to the number of highly active NAT2 genes.…”
Section: Tuberculosis and Isoniazidmentioning
confidence: 99%
“…NAT2 acetylates other arylamine-acceptor structures, such as isoniazid, caffeine, procainamide, and sulfasalazine (Grant et al 1983;Hughes et al 1954;Reidenberg 1984;Sabbagh et al 1997). Specific types of NAT1 and NAT2 alleles have been correlated with distinct metabolic activities, and also with the presence or absence of side effects for these drugs Lin et al 1998;Grant et al 1997Grant et al , 2000Hein et al 1994Hein et al , 2000Leff et al 1999).…”
Section: Introductionmentioning
confidence: 99%
“…The arylamine Nacetyltransferases (NAT) mediate the acetylation of clinically relevant drugs and procarcinogenic chemicals with homocyclic and heterocyclic amine structures. Two isoforms, NAT1 and NAT2, are found in humans and are characterized by distinct tissue expression and pharmacological profiles (Grant et al, 2000). Whereas NAT2 has historically been associated with the rapid versus slow acetylator phenotype, the pharmacogenomic revolution has revealed that both NAT1 and NAT2 are highly polymorphic (Grant et al, 2000;Boukouvala and Fakis, 2005).…”
mentioning
confidence: 99%
“…Two isoforms, NAT1 and NAT2, are found in humans and are characterized by distinct tissue expression and pharmacological profiles (Grant et al, 2000). Whereas NAT2 has historically been associated with the rapid versus slow acetylator phenotype, the pharmacogenomic revolution has revealed that both NAT1 and NAT2 are highly polymorphic (Grant et al, 2000;Boukouvala and Fakis, 2005). As such, the genetic variation of NAT has been the basis for extensive epidemiological investigations into the role of NAT genotypes as modifying risk factors for the development of certain cancers because NAT, paradoxically, can both detoxify and bioactivate procarcinogenic arylamines (Hein, 2002(Hein, , 2006.…”
mentioning
confidence: 99%